An integrated approach to digital training of prospective primary school teachers - Olga G. Yaroshenko; Olena D. Samborska; Arnold E. Kiv (Academy of Cognitive and Natural Sciences, 2020)
The article emphasizes the importance of information and digital  technologies in pre-service training of primary school teachers, substantiates the  content and components of information and digital competence of prospective  primary school teachers. It points out that the main purpose of information and  digital training in the pedagogical higher educational institutions (HEI) is to  ensure the formation of digital competence of future primary school teachers, to  prepare them for developing primary students' digital literacy in classes on  various academic subjects, for active use of ICT in primary school teachers'  professional activities. An integrated approach to the modernization of  information and digital training of pre-service primary school teachers, which  covers the main forms of the educational process - training sessions, independent  work, practical training, and control activities is justified. The article presents the  results the pedagogical experiment aimed at testing the effectiveness of the  integrated approach to the modernization of information and digital training of  prospective primary school teachers. The results are determined by the level of  digital literacy and the ability of students in the control and experimental groups  to use information and digital technology in the educational process of primary  school.